Strategi Pemasaran Digital Dalam Upaya Meningkatkan Penjualan UMKM Melalui Marketplace Shopee (Studi Kasus Pada Toko Helm Perintis Terpercaya) - Suharyani, Suharyani; Toana, Rangga Dalu Aji (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Digitalization has significantly transformed economic activities, particularly in the area of marketing. The shift in marketing trends worldwide from conventional to digital is evidence of this digitalization. Digital marketing is very influential and needed by MSMEs in this post-pandemic era. Digital marketing is the most effective marketing medium for all types of businesses, including MSMEs. This study aims to analyze the impact of digital marketing strategies, determine the inhibiting and supporting factors, and overcome inhibiting factors in marketing products. This study employs a qualitative research method. Data was collected through interviews, observations, and documentation at Perintis Terpercaya Helmets Store. The researcher gathered information from various sources, including the store owner, employees, academic experts, marketplace users, and one of the product buyers. The results of this study indicate that digital marketing through the Shopee marketplace is more effective and can increase sales